Aquasomes : A Self Assembled Nanoparticulate Carrier Systems - Garg, Rahul Kumar; Patwa, Ayushi; Dashora, Ashok; Jain, Preeti (Asian Journal of Pharmaceutical Research and Development, 2013)
Aquasomes is one of the most recently develop drug delivery system these are nanoparticulate carrier systems but instead of being simple nanoparticles these are three layered self assembled structures, comprised of a solid phase nanocrystalline core coated with oligomeric film to which biochemically active molecules are adsorbed with or without modification. These structures are self assembled by non covalent and ionic bonds. The solid core provides the structural stability, while the carbohydrate coating protects against dehydration and stabilizes the biochemically active molecules. Alternatively aquasomes are called as “bodies of water" their water like properties protect and preserve fragile biological molecules, and this property of maintaining conformational integrity as well as high degree of surface exposure are exploited in targeting of bio-active molecules like peptide and protein hormones, antigens and genes to specific sites.